Digital Business Strategising in the context of Regulatory Uncertainty - the case of a Financial Services Provider in South Africa - Brown, Nancy (Department of Information Systems, 2021)
With the rise of digital technologies that have disrupted standard business models and created a new level of competition in the market, the need for digital business strategising that shapes the future of organisations and achieves digital transformation is high on the agenda of most firms. The added complexity of uncertainty in the regulatory environment regarding financial products and services, regulation of digital platforms and ongoing financial regulatory changes based on macro-economic turbulence, makes for a complex external environment within which businesses need to effectively compete and achieve performance targets. A qualitative, interpretive case study of a South African based global organisation is undertaken to explore and understand how organisations navigate the macro-environmental landscape while forging a digitally transformed future. The research uses thematic analysis to extract themes in the data collected from both IT and business leaders as they navigate the path of transitioning from traditional to digital business models in the context of regulatory uncertainty. The study provides insight into what is required for firms to achieve digital transformation, and demonstrates the influence that regulatory uncertainty has on the digital business strategising process of a firm. A conceptual model is developed that reflects the key drivers of digital transformation to achieve digital maturity and competitive advantage, and also represents the external influencing factors of regulatory uncertainty. The findings reveal a shift to a more tactical, combined top-down, bottom-up strategising practice with reliance on dynamic capabilities, strong leadership and innovation to overcome challenges of regulatory uncertainty.